Whole-genome sequencing identifies I-SceI-mediated transgene integration sites in Xenopus tropicalis snai2:eGFP line. Issue 5 (16th February 2022) - Wang, Jian; Lu, Congyu; Wei, Shuo
Abstract: Transgenesis with the meganuclease I-SceI is a safe and efficient method, but the underlying mechanisms remain unclear due to the lack of information on transgene localization. Using I-SceI, we previously developed a transgenic Xenopus tropicalis line expressing enhanced green fluorescent protein driven by the neural crest-specific snai2 promoter/enhancer, which is a powerful tool for studying neural crest development and craniofacial morphogenesis. Here, we carried out whole-genome shotgun sequencing for the snai2:eGFP embryos to identify the transgene integration sites. With a 19x sequencing coverage, we estimated that 6 copies of the transgene were inserted into the Xenopus tropicalis genome in the hemizygous transgenic embryos. Two transgene integration loci adjacent to each other were identified in a noncoding region on chromosome 1, possibly as a result of duplication after a single transgene insertion. Interestingly, genomic DNA at the boundaries of the transgene integration loci contains short sequences homologous to the I-SceI recognition site, suggesting that the integration was not random but probably mediated by sequence homology. To our knowledge, our work represents the first genome-wide sequencing study on a transgenic organism generated with I-SceI, which is useful for evaluating the potential genetic effects of I-SceI-mediated transgenesis and further understanding the mechanisms underlying this transgenic method.